Towards an optimal design of target for tsetse control: comparisons of novel targets for the control of Palpalis group tsetse in West Africa. - Jean Baptiste Rayaisse; Johan Esterhuizen; Inaki Tirados; Dramane Kaba; Ernest Salou; Abdoulaye Diarrassouba; Glyn A Vale; Michael J Lehane; Stephen J Torr; Philippe Solano (Public Library of Science (PLoS), 2011)
BACKGROUND: Tsetse flies of the Palpalis group are the main vectors of sleeping sickness in Africa. Insecticide impregnated targets are one of the most effective tools for control. However, the cost of these devices still represents a constraint to their wider use. The objective was therefore to improve the cost effectiveness of currently used devices. METHODOLOGY/PRINCIPAL FINDINGS: Experiments were performed on three tsetse species, namely Glossina palpalis gambiensis and G. tachinoides in Burkina Faso and G. p. palpalis in Côte d'Ivoire. The 1 × 1 m(2) black blue black target commonly used in W. Africa was used as the standard, and effects of changes in target size, shape, and the use of netting instead of black cloth were measured. Regarding overall target shape, we observed that horizontal targets (i.e. wider than they were high) killed 1.6-5x more G. p. gambiensis and G. tachinoides than vertical ones (i.e. higher than they were wide) (P < 0.001). For the three tsetse species including G. p. palpalis, catches were highly correlated with the size of the target. However, beyond the size of 0.75 m, there was no increase in catches. Replacing the black cloth of the target by netting was the most cost efficient for all three species. CONCLUSION/SIGNIFICANCE: Reducing the size of the current 1*1 m black-blue-black target to horizontal designs of around 50 cm and replacing black cloth by netting will improve cost effectiveness six-fold for both G. p. gambiensis and G. tachinoides. Studying the visual responses of tsetse to different designs of target has allowed us to design more cost-effective devices for the effective control of sleeping sickness and animal trypanosomiasis in Africa.